2020
DOI: 10.1002/jbt.22617
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of zinc in liver damage in experimental diabetes demonstrated via different biochemical parameters

Abstract: Diabetes mellitus is a serious worldwide metabolic disease, which is accompanied by hyperglycaemia and affects all organs and body system. Zinc (Zn) is a basic cofactor for many enzymes, which also plays an important role in stabilising the structure of insulin. Liver is the most important target organ after pancreas in diabetic complications. In this study, we aimed to investigate the protective role of Zn in liver damage in streptozotocin (STZ)‐induced diabetes mellitus. There are four experimental groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…ADA activity increased in both tissues of the diabetic group (Figure 1). Current findings are supported by many studies that were found a significant elevation in ADA activity in tissues of STZ-induced diabetic rats (28)(29)(30). It has been stated that in type 2 diabetes, ADA activities are mainly raised which has a positive correlation with glycemic parameters (26).…”
Section: Discussionsupporting
confidence: 75%
“…ADA activity increased in both tissues of the diabetic group (Figure 1). Current findings are supported by many studies that were found a significant elevation in ADA activity in tissues of STZ-induced diabetic rats (28)(29)(30). It has been stated that in type 2 diabetes, ADA activities are mainly raised which has a positive correlation with glycemic parameters (26).…”
Section: Discussionsupporting
confidence: 75%
“…In the alloxan-induced diabetic rats, weak antioxidant enzymatic activities, elevated lipid peroxidation, and lowered nonenzymatic antioxidant levels were reported in previous studies [68][69][70][71]. To protect the body against ROS-mediated oxidative damage, antioxidant enzymes are released including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and glutathione reductase (GR) [72].…”
Section: Discussionmentioning
confidence: 99%
“…34 Similarly, vitamin U mitigate either amiodarone or D-galactosamine-induced hepatotoxicity, oxidative damage, as well as distortion of glycan levels. 35 Sacan et al 36 (2021) and Turkyilmaz et al 37 (2021) have demonstrated that antioxidant and antiinflammatory elements such as zinc could protect against cellular damage induced by streptozotocin. It also prevented oxidative stress and maintained normal levels of glycoconjugates.…”
Section: Discussionmentioning
confidence: 99%